Analysis of Archery Athlete Development Management in Improving Performance and Achievement in Jambi City - i, safi; ermaini; Ade Irma Suryani (PT. BERBAGI TEKNOLOGI SEMESTA, 2025)
This study aims to analyze the management of archery athlete development in improving performance and achievement in Jambi City. This study uses a descriptive qualitative approach with a focus on the coaching patterns implemented by archery clubs, coaches, and support from the Indonesian National Sports Committee (KONI) Jambi. Data collection was conducted through observation, in-depth interviews with coaches, athletes, and club administrators, and documentation of training and performance coaching activities. The results of the study indicate that the management of archery athlete development in Jambi City has been implemented systematically, but several obstacles remain, such as limited training facilities, inconsistent funding, and a lack of certified coach development programs. An effective coaching strategy involves performance-based training planning, regular evaluation of athlete performance, and improvement of coach competency. Synergy between KONI, clubs, and coaches is a key factor in optimizing the performance of archery athletes in Jambi City. This study is expected to provide recommendations for regional policymakers and coaches in improving the quality of athlete development in a sustainable manner..